0528 Development of Pediatric OSA Health Communication Messaging for and with Parents. (25th May 2022) - Honaker, Sarah; McQuillan, Maureen; Binion, Kelsey; Brann, Maria
Abstract: Introduction: Pediatric obstructive sleep apnea (OSA) is often undetected, due in part to gaps in parental awareness of OSA symptoms. To activate parents to talk to their child's provider about OSA symptoms, there is a need for effective OSA health communication messaging. Methods: We developed a health communication message in the form of an infographic, designed to help parents recognize the link between nighttime and daytime OSA symptoms. The message encouraged parents who saw these symptoms in their child to speak with their child's provider. The infographic was iteratively reviewed, rated, and refined through a series of twelve virtual focus groups with three types of stakeholder: parents of children with OSA symptoms (n=24), primary care providers (n=9), and sleep medicine specialists (n=4). During groups, we elicited reactions and asked participants to rate various aspects of the message. Results: Stakeholder feedback (semi-structured sessions and anonymous ratings) was elicited for the initial draft and two subsequent iterations of the message that incorporated prior feedback. Anonymous stakeholder ratings were measured on a scale from 1-5, with 5 denoting stronger endorsement of the construct. Parents rated the message positively for content (M=4.77; SD=0.44), literacy demand (M=4.92, SD=0.28), graphics/design (M=4.69, SD=0.63), and activation (M=4.77, SD=0.44). Sleep medicine providers perceived the message as accurate (M=5.0, SD=0) and primary care providers rated it as acceptable (M=4.67, SD=0.58) and feasible (M=4.33, SD=0.58) for display and dissemination in primary care settings. Conclusion: We developed a pediatric OSA health communication message that was rated highly by parents, primary care providers, and sleep medicine specialists. Next steps are to disseminate and evaluate the impact of the message on pediatric OSA detection. Support (If Any): Research reported in this publication was supported by the National Heart, Lung, and Blood Institute of the National Institutes of Health under Award Number K23HL150299. The content is solely the responsibility of the authors and does not necessarily represent the official views of the National Institutes of Health.